Makna Budaya Topa Ma Ta Auba pada Masyarakat Desa Lasi, Kecamatan Kuanfatu, Kabupaten Timor Tengah Selatan - Manek, Agnes Odiyanti (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2021)
Top ma ta auba is one of the traditions and customs of the people of Lasi Village, Kuanfatu Subdistrict, South Central Timor District